The design, construction, and commissioning of the KATRIN experiment. (17th August 2021) - Aker, M.; Altenmüller, K.; Amsbaugh, J.F.; Arenz, M.; Babutzka, M.; Bast, J.; Bauer, S.; Bechtler, H.; Beck, M.; Beglarian, A.; Behrens, J.; Bender, B.; et al.
Abstract: The KArlsruhe TRItium Neutrino (KATRIN) experiment, which aims to make a direct and model-independent determination of the absolute neutrino mass scale, is a complex experiment with many components. More than 15 years ago, we published a technical design report (TDR) [1] to describe the hardware design and requirements to achieve our sensitivity goal of 0.2 eV at 90% C.L. on the neutrino mass. Since then there has been considerable progress, culminating in the publication of first neutrino mass results with the entire beamline operating [2]. In this paper, we document the current state of all completed beamline components (as of the first neutrino mass measurement campaign), demonstrate our ability to reliably and stably control them over long times, and present details on their respective commissioning campaigns.